Improved thermal and mechanical properties of kenaf fiber/ ABS polymer composites via resin coating treatment - Owen, Macaulay Mfon (UPM Press, 2023)
In developing natural fiber composites (biocomposites), compatibility between natural cellulosic fibers and polymers has always created serious challenges, reducing performance. This study focused on applying a novel approach using epoxy resin as a coating medium to enhance the properties of the fibers and the interface between the hydrophobic polymer and the hydrophilic natural fiber. 10 wt% of uncoated kenaf fibers (KF) and coated kenaf (CKF) fibers were compounded with acrylonitrile butadiene styrene (ABS) thermoplastic polymer in a twin-screw extruder at an optimized temperature of 220°C under the same processing conditions. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) examined the coated and uncoated fibers' physicochemical compositions and surface properties. The developed composites' thermal, mechanical, and microstructural characteristics were also examined, and the results revealed that the CKF/ABS composites had better interfacial bonding and mechanical characteristics than the uncoated KF/ABS composite. Coating natural fibers with epoxy resin is a novel technique for improving interfaces and developing environmentally friendly composites from natural sources.